Pemberdayaan Kelompok Tenun Subi Melalui Penerapan Alat Tenun Bukan Mesin (Atbm) Di Desa Salubomba Kabupaten Donggala - hendra pribadi; Sayani; Marjun (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance the production capacity and quality of Donggala woven fabric through the implementation of Non-Machine Weaving Tools (ATBM) in the SUBI weaving group in Salubomba Village, Donggala Regency. The method used was the Participatory Technology Development (PTD) approach, involving active participation of partners in each phase of the activity. The activities included socialization, technical and non-technical training, technology application, post-program mentoring, evaluation, and sustainability strategies. The results showed significant improvements in production volume, product quality, and group management systems. Production increased from 70 to 168 sheets per year, the quality of natural dyes improved and became more durable, and marketing expanded through digital and conventional channels. The program contributed to improving community welfare and preserving local cultural heritage.